2012
DOI: 10.5194/acp-12-4867-2012
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotope fractionation during heterogeneous oxidation of SO<sub>2</sub> on mineral dust

Abstract: Abstract. Mineral dust is a major fraction of global atmospheric aerosol, and the oxidation of SO 2 on mineral dust has implications for cloud formation, climate and the sulfur cycle. Stable sulfur isotopes can be used to understand the different oxidation processes occurring on mineral dust. This study presents measurements of the 34 S/ 32 S fractionation factor α 34 for oxidation of SO 2 on mineral dust surfaces and in the aqueous phase in mineral dust leachate. Sahara dust, which accounts for ∼60 % of globa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 81 publications
(153 reference statements)
4
73
1
2
Order By: Relevance
“…In contrast, coarse mineral dust became enriched in 32 S as it passed through the cloud, consistent with isotope fractionation during SO 2 removal. Transition metal ions from mineral dust leachate cause very fast oxidation of SO 2 (Tilly et al, 1991;Rani et al, 1992;Harris et al, 2012a), and the efficiency of oxidation by this pathway means that, despite the relatively low number concentration of these particles compared to, for example, mixed particles, they are able to account for the majority of in-cloud SO 2 oxidation at Schmücke (discussed further in Harris et al (2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, coarse mineral dust became enriched in 32 S as it passed through the cloud, consistent with isotope fractionation during SO 2 removal. Transition metal ions from mineral dust leachate cause very fast oxidation of SO 2 (Tilly et al, 1991;Rani et al, 1992;Harris et al, 2012a), and the efficiency of oxidation by this pathway means that, despite the relatively low number concentration of these particles compared to, for example, mixed particles, they are able to account for the majority of in-cloud SO 2 oxidation at Schmücke (discussed further in Harris et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…The δ 34 S of the sulfate that could be added from each potential source was calculated from the upwind isotopic composition of SO 2 or H 2 SO 4 and the fractionation factors shown in Table 2. For SO 2 removal, the fractionation factors for SO 2 oxidation from Harris et al (2012a, b) were used with the Rayleigh fractionation laws to account for depletion of the SO 2 reservoir (Mariotti et al (1981); ; fraction of SO 2 oxidised determined in Harris et al, 2013). The δ 34 S values of the sulfate that would be added by each source are shown in Table 4 and Fig.…”
Section: Isotopic Composition Of Particulate Sulfatementioning
confidence: 99%
“…The reacted or aged mineral dust particles mainly included "reacted CaCO 3 / CaMg(CO 3 ) 2 " and "aluminosilicate + (N, S)", where the (N, S) notation represents compounds containing either nitrates, sulfates, or both. They were either produced when mineral dust particles (particularly Cacontaining species) react with airborne SO 2 and NO x in the presence of moisture or with "secondary acids" such as H 2 SO 4 , HNO 3 , and HCl (Harris et al, 2012;Wang et al, 2005), or were formed from the adsorption of NH 4 NO 3 and/or (NH 4 ) 2 SO 4 / NH 4 HSO 4 on the particle surface (Sullivan et al, 2007). In the present study, the overall relative abundance of mineral dust particles was more than 88 % of the particles analyzed for sample S1 collected in Beijing.…”
Section: Mineral Dust Particlesmentioning
confidence: 99%
“…Recently, Harris et al examined that sulphur isotope undergoes fractionation during oxidation of SO 2 in the gas phase, liquid phase and on mineral dust particle surfaces using NanoSIMS of collected products [122,123]. Oxidation of sulphur dioxide to sulphate is an important reaction in atmospheric chemistry [124].…”
mentioning
confidence: 99%
“…It follows that isotope ratio measurements may be useful for distinguishing metal-catalysed oxidation of SO 2 from other competing pathways. Another study by Harris et al demonstrated that sulphur isotope fractionation can be used for understanding the kinetics and mechanisms of SO 2 oxidation by mineral dust [122]. Sulphur isotope fractionation during heterogeneous oxidation of SO 2 on Sahara dust particles was characterised by a substantially larger fractionation factor (α = 1.0096) than aqueous oxidation in Sahara dust leachate (α = 0.9917).…”
mentioning
confidence: 99%